O INSTITUTO FEDERAL DE EDUCAÇÃO, CIÊNCIA E TECNOLOGIA DO ACRE E OS CURSOS INTEGRADOS PRÉ E PÓS REFORMA DO ENSINO MÉDIO. - de Lima Silva, Camila Caroline; de Fátima Melo, Lúcia; Fernanda Hojas, Viviani (Muiraquitã: Revista de Letras e Humanidades, 2020)
This text presents part of the results of a master's research that aimed to analyze the initial repercussions of Law No. 13,415 / 2017, which provides for High School Reform, in the integrated technical courses of the Federal Institute of Education, Science and Technology of the Acre (IFAC) - Campus Rio Branco and the conceptions of its professionals about this "new" policy. This section focuses on the analysis of the legislation on public policies for the offer of Integrated High School (EMI), of the Pedagogical Projects of courses integrated to high school (Informatics, Internet Computing, Computer Networks and Buildings), as well as of other institutional documents. Such analysis brought up important questions for comparing the situation of technical courses integrated to high school pre and post High School Curriculum Reform.